Design of obstacle avoidance robot - Le Xin, Lee (2012)
Recently,there are many types of robots available in market, either in form of pets,Vóys, cleaners and etc. Robots are utilized in many applications to assist human-being. iihpurpose of this project is to develop an autonomous robot that can move by itself.Without continuous human guidance. This robot will be controlled using the SK40C controller board that used an infrared sensor, microcontroller PlC 18F4550 and also a dc geared motor and a 16x2 LCD screen. When the robot is on,the LCD screen will show "Avoidance robot ON" and the buzzer will sound a beep continued by a move forward.When it senses an obstacle in front,it will reverse and then either turn left or right depending on the left sensor or right sensor that detect the obstacle then it will continue to move forward.When it senses an obstacle at the left, the LCD screen will show "Obstacle at front,reversing",then followed by "Turn right, move forward".As a result,this robot is useful as a baby walker to avoid the baby walker from hitting thing that may cause harm to the baby.